MIMESIS, SUBLIME, CATHARSIS AND SYMPATHY IN THE SACRIFICE RITUAL AND THE SACRIFICE OF ISMAEL PAINTING FROM THE QAJAR SCHOOL - Apena Esfandiari (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This research analyzed the paradoxical aspects of sacrifice from a philosophical and non-religious point of view, its roots and types, by presenting an intellectual model and using valid theories. The transcendence and refinement that resulted from the introduction of violence against sacrifice in primitive societies later led to the transformation of human-animal sacrifice into a turning point in the mitigation of violence and became known as the process of rationalization. In the interdisciplinary philosophical-artistic study of the story of Abraham (pbuh), the model is the command of God, which from a religious point of view, following the model is independent of the result of action, sublime and transcendental. Sacrifice, especially of the blood type, is contradictory, even in the model of human-animal substitution, and in contrast to the feeling of sympathy and spiritual purification due to violence; But since the importance of the intention of the matter restores the judgment of the action and obedience to the model is obligatory, this takes on a sacred aura and becomes a sublimation; Because mimesis is a religious ritual, and this paradox in sacrifice is philosophically and non-religious.